2021
DOI: 10.1186/s12911-020-01362-0
|View full text |Cite
|
Sign up to set email alerts
|

CNFE-SE: a novel approach combining complex network-based feature engineering and stacked ensemble to predict the success of intrauterine insemination and ranking the features

Abstract: Background Intrauterine Insemination (IUI) outcome prediction is a challenging issue which the assisted reproductive technology (ART) practitioners are dealing with. Predicting the success or failure of IUI based on the couples' features can assist the physicians to make the appropriate decision for suggesting IUI to the couples or not and/or continuing the treatment or not for them. Many previous studies have been focused on predicting the in vitro fertilization (IVF) and intracytoplasmic sper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(20 citation statements)
references
References 48 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…The following studies can be shown as an example: Al-Waisy et al [ 72 ] achieved accuracy of 99.99%, Dhiman et al [ 79 ] achieved accuracy of 98.54%, Ozturk et al [ 14 ] achieved accuracy of 98.08%, and Ahuja et al [ 74 ] achieved accuracy of 99.4%. The main reason for the success of the mentioned studies is that the most common symptom of COVID-19 disease is lung involvement [ 80 ] and the symptoms can be clearly observed on radiographic lung images [ 81 ]. Despite this, some studies using CT and X-ray to diagnose COVID-19 have achieved less accuracy rate than our proposed method.…”
Section: Resultsmentioning
confidence: 99%
“…The following studies can be shown as an example: Al-Waisy et al [ 72 ] achieved accuracy of 99.99%, Dhiman et al [ 79 ] achieved accuracy of 98.54%, Ozturk et al [ 14 ] achieved accuracy of 98.08%, and Ahuja et al [ 74 ] achieved accuracy of 99.4%. The main reason for the success of the mentioned studies is that the most common symptom of COVID-19 disease is lung involvement [ 80 ] and the symptoms can be clearly observed on radiographic lung images [ 81 ]. Despite this, some studies using CT and X-ray to diagnose COVID-19 have achieved less accuracy rate than our proposed method.…”
Section: Resultsmentioning
confidence: 99%
“…Another pathway-based variant incorporates pathway data to group patients into cancer subtypes ( Mallavarapu et al, 2019 ). Additionally, in Jean-Quartier et al (2021) clustered GBM patients into several age subgroups with different age-related biomarkers. Finally, a work developed in Nguyen et al (2017) , named PINS, allows omics data integration and molecular patient stratification automatically.…”
Section: Machine Learning As a Source Of New Knowledgementioning
confidence: 99%
“…In consequence, the foremost deed is to assemble such a technique that could precisely detect COVID-19 during the early stage, in the shortest possible time. There have been many machine learning models that do detect COVID-19 automatically but shortfalls in time check, or even in accurate diagnosis of COVID-19 ( Muhammad, Algehyne, Usman, Ahmad, Chakraborty, Mohammed, 2021 , Müller, Ehlen, Valeske, 2021 , Rasheed, Hameed, Djeddi, Jamil, Al-Turjman, 2021 , Sun, Hong, Song, Li, Wang, 2021 ). As the planet scuffles with COVID-19, every ounce of technical creativity and imagination is deployed to combat this pandemic and bring COVID-19 to an end.…”
Section: Introductionmentioning
confidence: 99%